Extending ecocriticism : crisis, collaboration and challenges in the environmental humanities - Barry, Peter, 1947-; Welstead, William (Manchester University Press, 2017)
This book takes ecocriticism into new areas that include collaboration across the environmental humanities and into the cultural studies of the human response to the environment. The essays, by both early career and established researchers, are accessible enough to appeal to the general reader, but will be important supplementary reading for undergraduate and post-graduate students in the environmental humanities.